Isolation of Mycobacterium mageritense from the Lung of a Harbor Porpoise (Phocoena phocoena) with Severe Granulomatous Lesions - Morick, D.; Kik, M.; de Beer, J.; van der Zanden, A. G. M.; Houwers, D. J. (Journal of wildlife diseases, 2008)
Post-mortem investigation of a harbor porpoise (Phocoena phocoena) found dead on the beach of the island of Vlieland, The Netherlands, revealed severe granulomatous changes in the right lung lobe. Ziehl Neelsen staining demonstrated relatively large acid-fast rods. Mycobacterial culture yielded a fast-growing mycobacterium, which was identified by molecular biological methods as Mycobacterium mageritense. Autolysis prevented histopathology. It was tentatively concluded that the granulomatous changes were the cause of porpoise's death and that M. mageritense was the causative agent. This is the first report of the isolation and molecular identification of this mycobacterium in a nonhuman animal species and the first association with the marine environment.